Development and design of wearable textile antenna on various fabric substrate for unlicensed ultra-wideband applications - Nor Hadzfizah Mohd Radi; Mohd Muzafar Ismail; Zahriladha Zakaria; Jeefferie Abd Razak; Siti Nur Illia Abdullah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In the area of wearable technology an enhancement of basic microstrip antenna is evolution of wearable textile antenna. A major requirement for wearable textile antenna is its flexible designed materials which incoprates of fabric in the structure. The parameters obtained from the wearable textile antenna are return loss (S-11), directivity, gain, voltage standing wave ratio (VSWR) as well as the specific absorption rate (SAR) value. All these parameters are mostly influenced by the value of substrate dielectric constant and its thickness. In this paper, the design of wearable dual band frequency microstrip antenna is presented for wireless communication services. When the federal communication commission (FSS) has allowed the operation of unlicensed ultra-wideband (UWB) thus it attracted research interest in realizing UWB antennas for wireless applications. The operating frequency of the proposed antenna ranges from 2.85 GHz to 7.3 GHz. For body-worn and wearable applications, the antenna is embedded on selected textiles (i.e. felt, denim, polyester and leather). The prorposed microstrip antenna is designed, simulated and analysed in computer simulation technology (CST) microwave studio.